Leaving Tulsa - Foerster, Jennifer Elise (Sun tracks., 2013)
The poet weaves together a mythic and geographic exploration of a woman's coming of age in a dislocated time. This book, a book of road elegies and laments, travels from Oklahoma to the edges of the American continent through landscapes at once stark and lush, ancient and apocalyptic.